THE PILLARS OF GREEN MARKETING AND ITS ROLE IN ACHIEVING SUSTAINABLE COMPETITIVE ADVANTAGE A STUDY OF THE SAMARRA PHARMACEUTICAL COMPANY, IRAQ (World Economics and Finance Bulletin, 2025)
Green marketing is one of the most important areas addressed by modern marketing literature, adopted by most business organizations seeking to differentiate their products from conventional ones. The importance of this study lies in shedding light on a crucial issue: environmental protection, as well as how organizations can leverage the social and ethical dimensions to achieve material marketing gains and gain sustainable competitive advantages. This study aims to understand the relationship between the four pillars of green marketing—product, price, promotion, and distribution—and achieving sustainable competitive advantage, including quality, flexibility, creativity, customer responsiveness, cost, and efficiency, at the General Company for the Manufacture of Medicines and Medical Supplies in Samarra, Iraq
Keywords: Green marketing; sustainable competitive advantage; General Company for Pharmaceutical Industries